On two goby-associated snapping shrimps from the Red Sea, one of them new to science (Malacostraca: Decapoda: Alpheidae: Alpheus) - Anker, Arthur (Zootaxa, 2022)
Two snapping shrimps associated with gobies are reported from the Saudi Arabian coast of the Red Sea. Alpheus karplusi sp. nov., a species with a highly diagnostic, rusty-spotted colour pattern, is described based on three specimens, two males and one female, collected in the Farasan Islands and off Thuwal. Alpheus thompsoni Anker, 2022, previously known with certainty only from Papua New Guinea, is reported from the Farasan Islands, on the basis of a complete adult male specimen. Some differences in the colour pattern and morphology between the female holotype from Papua New Guinea and the male from the Red Sea are discussed. Both species belong to the A. djeddensis Coutière, 1897—A. djiboutensis De Man, 1909 species complex, which also includes A. bellulus Miya & Miyake, 1969, A. macellarius Chace, 1988, A. fenneri Bruce, 1994, A. mannarensis Purushothaman, Abhilash, Kumar & Lal, 2021, and A. sciolii Anker, 2022.